2005
DOI: 10.1111/j.1348-0421.2005.tb03735.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Human Fab Library and Isolation of Monoclonal Fabs with Rabies Virus‐Neutralizing Ability

Abstract: A combinatorial human Fab library was constructed using RNAs from peripheral blood lymphocytes of 6 rabies vaccine‐boosted volunteers using pComb3X phagemid vector. The size of the constructed library was approximately 7.0×107 Escherichia coli transformants. The library was selected against purified rabies virus (RV) virion or purified RV glycoprotein for isolation of phages displaying RV‐neutralizing human Fab antibody. Among 132 selected clones, two Fab preparations revealed neutralizing activities against R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…8 CFU E. coli transformants, which was considered to be good enough for an efficient isolation of a series of promising Fab molecules (2,23). The constructed phage library was panned three times on the purified JEV antigen so that a pool of phages displaying Fab molecule specifically interacts to the antigen would be enriched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 CFU E. coli transformants, which was considered to be good enough for an efficient isolation of a series of promising Fab molecules (2,23). The constructed phage library was panned three times on the purified JEV antigen so that a pool of phages displaying Fab molecule specifically interacts to the antigen would be enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Purified Fab molecule was prepared from TJE12B02 which showed the highest JEV strain Nakayama neutralizing activity, and the highest standardized value for antigen-binding activity to the same strain (Table 1). Approximately 1.0 mg of the purified FabTJE12B02 was obtained from 1.0 liter E. coli culture using the column coupled with anti-human F(ab') 2 (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] Due to their small size, rapid blood clearance, and low immunogenicity, Fab have been widely utilized in diagnostic, therapeutic, and research applications. [38,39] For example, Fab fragments have been employed in the treatment of digoxin ingestion,[40] snake bites,[41] Entamoeba histolytica ,[42] rabies,[43] thrombosis, and tumors. [44]…”
Section: Introductionmentioning
confidence: 99%
“…Rabies is a zoonotic viral disease that infects wild as well as domestic animals [1]. It is estimated that at least 500,000 people receive post-exposure vaccination and that 55,000 people die from rabies each year [2], especially in Africa and Asia where rabies is endemic, and where successful canine rabies vaccination or control programs have not been implemented [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ando et al. have reported two Fab preparations, EP5G3 and GD2D12, that were isolated from a phage display library, which have neutralizing activity against rabies virus strain CVS when assayed by rapid fluorescent focus inhibition test (RFFIT) [1]. Houimel et al also have reported three Fabs isolated from a recombinant immune antibody library [2].…”
Section: Introductionmentioning
confidence: 99%